Electron transfer phase transition and oxidization process in NaxCo0.44Mn0.56[Fe(CN)6]0.90 (0.00 ≤ x ≤ 1.60). Issue 100 (17th November 2021) - Iwaizumi, Hiroki; Shibata, Takayuki; Moritomo, Yutaka
Abstract : The electron transfer phase transition in Prussian blue analogues reverses the order of oxidation among Fe, Mn, and Co. Abstract : We investigated the phase diagram of Na x Co0.44 Mn0.56 [Fe(CN)6 ]0.90 in the entire Na concentration range of 0.00 ≤ x ≤ 1.60. We found that the compound shows an electron transfer (ET) phase transition in a wide x range of 0.19 ≤ x ≤ 1.38. The extended ET model well reproduces the variation of the [Fe 2+ (CN)6 ] 4− and [Fe 3+ (CN)6 ] 3− concentration at the phase transition. The ET phase transition reverses the oxidation process of the compound; the process is in the order of Co, Mn, and Fe (Fe, Mn, and Co) in the low (high) temperature phase.